A study on relationships between large‐scale climate indices and estimates of North Pacific albacore tuna productivity. (17th June 2014) - Zhang, Zane; Holmes, John; Teo, Steven L. H.
Abstract A logistic production model was used to examine potential relationships between three climate indices, the North Pacific Gyre Oscillation (NPGO), the Pacific Decadal Oscillation (PDO), and the Multivariate El Niño‐Southern Oscillation Index (MEI), and productivity estimates of the North Pacific albacore tuna (Thunnus alalunga) population. Catch and standardized catch‐per‐unit‐effort data from three longline fisheries (Japan, US, and Taiwan) were used in the model. The climate indices were incorporated into the model by correlating time‐varying intrinsic population growth rate (ry) of the production model with the annual mean value for each index. The estimated probability that the NPGO is positively correlated with stock productivity, as measured by ry, was 0.99, and the calculated probability that MEI is negatively correlated with the productivity was 0.95. The time lag for these correlations is 4 yr, which is consistent with the timing of recruitment to the Japan longline fishery. The PDO did not seem to have any detectable relationship with stock productivity. However, it remains uncertain if there is a conclusive linkage between the albacore productivity and the NPGO or the MEI index, because model fit to the data is about the same as that of a base model which does not use any climate index and assumes a time‐invariant r.